Sesi perjumpaan pengerusi lembaga pengarah UiTM bersama staf Arshad Ayub Graduate Business School - UiTM, Arshad Ayub Graduate Business School (Arshad Ayub Graduate Business School, 2023)
On 14th July 2023, Profesor Emeritus Datuk Dr Raduan Che Ros has visited Arshad Ayub Graduate Business School for a meeting session with the staff. Thank you for coming to Arshad Ayub Graduate Business School.